FAKTOR-FAKTOR YANG MEMPENGARUHI TINGGINYA PARTISIPASI POLITIK MASYARAKAT PADA PILKADES SERENTAK DI DESA BALAM JAYA KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2015 - Januardi Adlin; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is based on the election of village heads simultaneously in 2015 in accordance with Law Number 6 Year 2014 About the Village. The election of village heads simultaneously was also held in Balam Jaya Village, Tambang Sub District, Kampar District. At the time of the election of village chief Balam Jaya Year 2015, political participation Balam Jaya Village community is very high with many factors that influence it. Based on the background of the problem, this study aims to determine the factors that led to high political participation of the community in the Village Balam Jaya District Tambang Kampar regency in the election of village heads simultaneously in 2015. Research methods used in the writing of this thesis is Qualitative. Data type in this research is primary data and secondary data. Data collection techniques in this study are interviews and documentation. Data analysis technique used is descriptive qualitative.The results of this study indicate that the high political participation of the people of Balam Jaya in Village during the election of village heads simultaneously in 2015 is caused by many factors. Generally Balam Jaya villagers choose because of the factors of political mobilization, sociological factors, psychological factors and rational choice factors. However, one of the more dominant factors among these factors is sociological factors, where the influence of demographic and socio-economic backgrounds, such as gender, residence (city-village), occupation, education, class, income, and religion as well The existence of family relations is very influential on the election of village heads in the village of Balam Jaya. However, the overall factors contributing to the high level of political participation of the people are interrelated, as are political mobilization factors that are linked to the underlying factors of sociological, psychological and rational choice. It can be seen and analyzed from the answer informant research when conducting interviews in the field. Then in this study the authors conclude that the sociological factor is the biggest factor causing the high political participation of the community in the village of Balam Jaya, then the factor is also reinforced by other factors that also have considerable influence.Keywords: Unselected Behavior, Village Head Election